Normative criteria of mass media; A Comparative Study of Neoliberalism and Imam Khomeini's Approach - Mohammad Reza Rowhani (Religion & Communication)
Among mass communication theories, there is a set of normative theories, which describes the do's and don'ts of mass media in different societies; the division of Sibert et al. Is the first of its kind. Meanwhile, the liberal approach has been accompanied by significant ups and downs to date, the result of which can be followed in the formation of the neoliberal theory or the theory of social responsibility of the mass media; undoubtedly, social responsibility in its improvisation is a general and valuable concept. But this meaning in the theoretical literature of mass media is not in conflict with the traditional liberalist approach in terms of principles and follows the mentioned path in a different formulation; therefore, despite the value of this concept, this theoretical literature cannot be used in the context of religious approach to the media. This article, along with documentary studies, in reviewing and comparing with the basics and principles of neoliberal media, while purposeful sampling based on directional deductive qualitative content analysis, will explain the view of Imam Khomeini, may God have mercy on him; Accordingly, the media of the level of the Islamic Revolution in the thought of Imam (may God have mercy on him), while overcoming the shortcomings of the neoliberal media, showed the structural and content possibilities of the religious media for the excellence and growth of man and society. Defines the do's and don'ts of mass media in the light of Islamic culture and in order to achieve divine responsibility.